Klotho Deficiency Causes Heart Aging via Impairing the Nrf2-GR Pathway. Issue 4 (19th February 2021) - Chen, Kai; Wang, Shirley; Sun, Qiwei Wilton; Zhang, Bo; Ullah, Mujib; Sun, Zhongjie
Abstract : Rationale: Cardiac aging is an important contributing factor for heart failure, which affects a large population but remains poorly understood. Objective: The purpose of this study is to investigate whether Klotho plays a role in cardiac aging. Methods and Results: Heart function declined in old mice (24 months), as evidenced by decreases in fractional shortening, ejection fraction, and cardiac output. Heart size and weight, cardiomyocyte size, and cardiac fibrosis were increased in old mice, indicating that aging causes cardiac hypertrophy and remodeling. Circulating Klotho levels were dramatically decreased in old mice, which prompted us to investigate whether the Klotho decline may cause heart aging. We found that Klotho gene mutation (KL−/−) largely decreased serum klotho levels and impaired heart function. Interestingly, supplement of exogenous secreted Klotho prevented heart failure, hypertrophy, and remodeling in both old mice and KL (−/−) mice. Secreted Klotho treatment inhibited excessive cardiac oxidative stress, senescence and apoptosis in old mice and KL (−/−) mice. Serum phosphate levels in KL (−/−) mice were kept in the normal range, suggesting that Klotho deficiency-induced heart aging is independent of phosphate metabolism. Mechanistically, Klotho deficiency suppressed GR (glutathione reductase) expression and activity in the heart via inhibition of transcription factor Nrf2 (nuclear factor-erythroid 2 p45-related factor 2). Furthermore, cardiac-specific overexpression of GR prevented excessive oxidative stress, apoptosis, and heart failure in both old and KL (−/−) mice. Conclusions: Klotho deficiency causes cardiac aging via impairing the Nrf2-GR pathway. Supplement of exogenous secreted Klotho represents a promising therapeutic strategy for aging-associated cardiomyopathy and heart failure. Abstract : Supplemental Digital Content is available in the text.